Optimalisasi Sumber Daya Alam untuk Meningkatkan Ekonomi Kota Medan - Bonaraja Purba; Vivi Safira; Mentari Rezeki Ramadhani; Meutia Fahrani; Zulfa 'Afifah (Economic Reviews Journal, 2024)
This research aims to evaluate the use of Medan City's natural potential as the main driver of the economy. As a country that has abundant natural wealth, Medan has a great opportunity to direct economic growth in a more advanced and sustainable direction. Through a qualitative approach, this research explores various literature sources, including data from BPS, scientific journals, and other related literature. These findings highlight that although various programs and policies have been implemented, optimal use of natural resources in Medan, especially in the Fisherman's Village area, is still far from expectations. This fact is reflected in the low income of traditional fishing communities which only reaches around Rp. 1,429,551 per month. Therefore, this research emphasizes the need for more effective strategies in managing natural resources so that they can have a significant positive impact on the economy in Medan City.